Dose and robustness comparison of nominal, daily and accumulated doses for photon and proton treatment of sinonasal cancer. (August 2022) - Argota-Perez, R.; Sharma, M.B.; Elstrøm, U.V.; Møller, D.S.; Grau, C.; Jensen, K.; Holm, A.I.S.; Korreman, S.S.
Highlights: Photon and proton treatment of sinonasal cancer patient have different strengths regarding OAR sparing. Photon and proton treatment of sinonasal cancer is robust towards anatomical variations for both treatment modalities. Patient selection for either proton or photon treatment of sinonasal cancer should be based on a case-by-case comparison. Abstract: Introduction: The aim was to evaluate and compare the dosimetric effect and robustness towards day-to-day anatomical and setup variations in the delivered dose for photon and proton treatments of sinonasal cancer (SNC) patients. Materials and Methods: Photon (VMAT) and proton (IMPT) plans were optimized retrospectively for 24 SNC patients. Synthetic CTs (synCT) were obtained by deforming the planning CT (pCT) to the anatomy of every daily cone-beam CT. Both VMAT and IMPT plans were recalculated on the synCTs. The recalculated daily dose was accumulated over the whole treatment on the pCT. Target coverage and dose to organs and risk (OARs) were evaluated for all patients for the nominal, daily and accumulated dose distribution. Results: In general, dose to OARs farther away from the target, including brain, chiasm and contralateral optic nerve, was lower for proton plans than photon plans. Whereas, OARs in proximity of the target received a lower dose for photon plans. For proton plans, the target coverage (volume of CTV receiving 95% of prescribed dose), V95%, fell below 99% for 9/24 patients in one or more fractions. For photon plans, 4/24 patients had one or more fractions where V95% fell below 99%. For accumulated doses, V95% was below 99% only in two cases, but above 98% for all patients. Conclusion: Photon and proton treatment have different strengths regarding OAR sparing. The robustness was high for both treatment modalities. Patient selection for either proton or photon radiation therapy of SNC patients should be based on a case-by-case comparison.